Zinc improves mitochondrial respiratory function and prevents mitochondrial ROS generation at reperfusion by phosphorylating STAT3 at Ser727. (May 2018) - Zhang, Ge; Sheng, Mingwei; Wang, Jiannan; Teng, Tianming; Sun, Yuemin; Yang, Qing; Xu, Zhelong
Abstract: Serine 727 (Ser 727 ) phosphorylation of STAT3 plays a role in the regulation of mitochondrial respiration. This study aimed to test if zinc could regulate mitochondrial respiration through phosphorylation of STAT3 at Ser 727 in the setting of ischemia/reperfusion in the heart. Under normoxic conditions, treatment of isolated rat hearts with ZnCl2 increased cytosolic STAT3 phosphorylation at Ser 727 followed by phospho-STAT3 translocation to mitochondria. In isolated rat hearts subjected to 30 min regional ischemia followed by 20 min of reperfusion, ZnCl2 given 5 min before the onset of reperfusion also increased mitochondrial phospho-STAT3. ZnCl2 enhanced ERK phosphorylation and PD98059 reversed the effect of ZnCl2 on STAT3 phosphorylation. ZnCl2 improved the mitochondrial oxidative phosphorylation at reperfusion. This effect was abolished by STAT3S727A, a mutant in which Ser 727 is replaced with alanine, in H9c2 cells subjected to hypoxia/reoxygenation. In addition, ZnCl2 increased the mRNA level of the complex I subunit ND6, which was also reversed by STAT3S727A. Moreover, ZnCl2 attenuated mitochondrial ROS generation and dissipation of mitochondrial membrane potential (ΔΨm) at reoxygenation through Ser 727 phosphorylation. Finally, ZnCl2 suppression of succinate dehydrogenase (SDH) activity upon the onset of reperfusion was nullified by the Ser 727 mutation. In conclusion, zinc improves cardiac oxidative phosphorylation and inhibits mitochondrial ROS generation at reperfusion by increasing mitochondrial STAT3 phosphorylation at Ser 727 via ERK. The preservation of ND6 mtDNA and the inhibition of SDH activity may account for the role of STAT3 in the beneficial action of zinc on the mitochondrial oxidative phosphorylation and ROS generation at reperfusion. Graphical abstract: Highlights: Zinc induces STAT3 phosphorylation at Ser 727 via ERK and translocates it into mitochondria. Zinc improves oxidative phosphorylation and inhibits ROS generation at reperfusion. Preservation of ND6 mtDNA and inhibition of SDH through STAT3 may account for the action of zinc.